Biomechanical comparison of pullout strengths of six pedicle screws with different thread designs - Karakaşlı, Ahmet (Jt Dis Relat Surg, 2021)
OBJECTIVES: This study aims to assess the pullout strength of six different pedicle screw thread patterns. MATERIALS AND METHODS: A total of 36 sheep spines were divided into six groups including six spines in each group: fully threaded cortical (Type A), fully threaded spongeous (Type B), fully cortical threads in the proximal half and fully spongeous threads in the distal half (Type C), fully spongeous threads in the proximal half and fully cortical threads in the distal half (Type D), unthreaded proximal half with fully spongeous threads in the distal half (Type E), and unthreaded proximal half with fully cortical threads in the distal half (Type F). The axial compression-traction machine was used for biomechanical testing at a pullout rate of 1 mm/min. RESULTS: The mean values of pullout strength of the groups A, B, C, D, E, and F were 1112±7.52 N, 986±8.34 N, 646±3.88 N, 676±7.16 N, 609±9.52 N, and 769±6.49 N, respectively. There was a statistically significant difference between the screw groups A and B, C, D, E and F (p=0.036, p=0.028, p=0.04, p=0.039, and p=0.046, respectively). A statistically significant difference was observed between the groups B versus C and E (p=0.037 and p=0.021, respectively). There was no statistically significant difference between the groups B versus D and F (p=0.35 and p=0.61, respectively). CONCLUSION: Fully threaded cortical pedicular screw design exhibited the strongest bone grasp compared to other thread designs. Further studies should be conducted in multidirectional force pattern on human spine to assess the six screw thread designs in a closer real-life setting simulation model.